Do pigs like to brush? An observational study of pig brushing behaviour in a commercial production environment - Högberg, Niclas; Skånberg, Lena; Guzhva, Oleksiy; Westin, Rebecka; Sannö, Axel; Wallenbeck, Anna; Rørvang, Maria Vilain (Frontiers in Animal Science, 2025)
IntroductionIn semi-natural environments, pigs have been observed rubbing or scratching against trees and bushes, and in commercial settings, they often rub against pen structures and may allow handlers to scratch them. Whilst human-applied scratching of pigs has been studied, little is known about their self-scratching behaviour. Research on brush use in cattle suggests potential welfare benefits, while research on brushing behaviour in pigs is, to the best of our knowledge, absent. To address this gap, this study investigated whether gestating sows use a mechanical brush when housed in a social setting; how brushing varied in duration, frequency, body region, and time of day; and whether individuals differed in brush use.Materials and methodsThe study was conducted on 29 loose-housed gestating Yorkshire sows with access to deep straw bedding, a transponder-controlled feeder, and a mechanical brush (Comfort Pig, Comfy-Solutions B.V., Roelofarendsveen, the Netherlands). Observations included 192 h of continuous video recordings covering the brush area. An ethogram adapted from cattle studies and refined for pigs was applied to record brushing, sniffing, oral manipulation, and displacements. Brushing was further categorised by body region, initiation, intensity, and duration. Data were summarised descriptively, and differences between groups, times, and individuals were assessed using nonparametric methods.ResultsAll sows engaged in brushing at least once, during the study, averaging 1.5 (interquartile range, IQR = 1–2) bouts per day. The median bout duration was 12 s (IQR = 8–17), with active brushing comprising nearly half of the total time. Brushing was mainly directed to the middle body region (29.8%) and often initiated at the head (46.2%). No consistent diurnal pattern was evident. Sniffing preceded brushing in 85 of the 297 observed brushing bouts, whilst oral manipulation was only observed five times. Incomplete bouts and occasional displacements (3% of bouts) suggest that internal and social factors may influence access.ConclusionTaken together, this study provides an initial systematic description of the brushing behaviour in pigs and suggests that mechanical brushes may serve as an enriching resource for pigs in production. Further research, including comparisons across different brush types, production stages, pig-to-brush ratios, and housing systems, is needed to evaluate their potential as welfare-enhancing tools in commercial pig production.